DEMOCRATIZATION OF POLITICAL COMMUNICATION AND POLITICAL PARTICIPATION WITH USING E-DEMOCRACY TECHNOLOGY - I. S. Shirokov (Современная наука и инновации)
Over the past several years, governments across the democratic spectrum have repeatedly resorted to excessive oversight and discriminatory restrictions on freedoms, movement, and mass gatherings. Violent restrictions by non-state actors were applied. A large amount of false information, in some cases deliberately created by political leaders, concealed reliable information and misled hundreds of citizens. There was a need to maintain stable democracy and new forms of its manifestation. Such a task requires balanced legislation and institutions to protect against the accumulation of power in the hands of the minority.